Variation among young individuals of Bothrops neuwiedi complex (Serpentes, Viperidae, Crotalinae) - Xavier, Vinícius (Phyllomedusa: Journal of Herpetology, 2002)
Variation among young individuals of Bothrops neuwiedi complex (Serpentes, Viperidae, Crotalinae). External morphological charactcrs of 141 young specimens (69 males and 72 females) of the Bothrops neuwiedi complex were analyzed. Regression analysis was used in the study of morphometric characters and principal component analysis was used in the study of meristic and qualitative charactcrs. Sexual dimorphism was confirmed in the meristic and morphometric characters. Males showed higher counts of subcaudals and longer tails. Females showed eventually higher number of vendais and dorsal rows, and larger heads. Six different drawing patterns were diagnosed and can indicate the existence of different spccics. Ontogenetic variation was described.